Equilibrium in Monopolistic Competition: An Addendum - Smithies, A. (Quarterly Journal of Economics, 1942)
Journal Article Equilibrium in Monopolistic Competition: An Addendum Get access A. Smithies A. Smithies University of Michigan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 56, Issue 2, February 1942, Pages 332–336, https://doi.org/10.2307/1881936 Published: 01 February 1942